Interaction between nitrogen fertilization, rainfall and groundwater pollution in sandy soil - Yusop, Mohd Khanif; Van Cleemput, Oswald; Baert, Leen (Springer Netherlands, 1984)
A 2 yr field study on the influence of N fertilization and rainfall on groundwater pollution was carried out in the sandy area of Belgium. The NO inf3 sup− -N and Cl− content of the groundwater at 0.5, 1.0, 1.5, and 2.0 m depths was monitored every two weeks on a field, grown with barley in 1980 and with maize in 1981. Turnips for cattle feed were grown in between the two crops. The total annual rainfall during the period under study was about 800 mm. The NO inf3 sup− -N content at all depths was at all times above 11.3 mg NO inf3 sup− -N dm−3, the WHO safe limit. Fluctuation of the NO inf3 sup− -N content occurred mainly at 0.5 and 1.0 m. The concentration at 1.5 and 2.0 m depths was higher most of the time than at 0.5 and 1.0 m. Leaching of NO inf3 sup− -N into deeper layers occurred when there was heavy rainfall. There was no important loss of NO inf3 sup− -N through denitrification at 1.5 and 2.0 m depths.